INVESTIGATION ON THE EFFECT OF TSUNAMI WAVES ON INTEGRITY OF TARPON MONOPOD IN MALAYSIAN WATERS - Hashim, Nur Aqilah (Universiti Teknologi PETRONAS, 2018)
This paper presents the structural sensitivity analysis of tarpon monopod structure subjected to tsunami waves benchmarked against storm metocean conditions. Malaysia's geographical location situated on a seismically stable, partially protected from risks of tsunami, thus, general practice in the design of fixed offshore platforms in Malaysia are governed primarily by the wave forces at the sea without taking into consideration of tsunami loading. However, 9.3Mw seaquakes occurred off Northwest Coast of Aceh on December 2004 had led to generated tsunami waves which caused dozens of fatalities and billions to restructure the damages. Hence, it has brought the attention to the needs of examining the integrity of offshore structures scattered throughout Malaysian waters as these platforms are being exposed to tsunami threat coming from Manila Trench.